Gender Differences in Structuring Spoken Personal Experiences amongst Vocational High School EFL Students (A Study at SMK Negeri 3 Padang - Yuliana Fitri; Hamzah Hamzah (Universitas Negeri Padang, 2022)
Although there have been many studies that have analysed gender differences, only a few studies have compared the differences between male and female students in structuring spoken personal experience, according to the use of generic structure. This research aimed to analyse how gender differences in structuring the spoken experience based on the use of generic structure. This research used descriptive method and used speaking task as instrument. The sample was ten male students and ten female students from the first grade students of SMK Negeri 3 Padang in the academic year 2021/2022. This research used the Labov’s narrative theory to analyse the data. The result of this research showed that they tended to put more focus in the using of orientation, complicating action, and coda, and they paid less attention in the use of abstract, evaluation and resolution in structuring the spoken experience. Furthermore, both of students tended to be more complete on complicating action element (100%), while the male students tended to be very incomplete on abstract element (40%) and the female students tended to be very incomplete on evaluation element (10%).